Practice makes perfect French verb tenses - Booth, Trudie Maria (New York McGraw-Hill, 2023)
"The book is divided into four main parts:
Part I works with the present tense, including the conjugation of regular and irregular verbs, asking questions, impersonal verbs, and the use of reflexive verbs. Idiomatic uses of avoir, faire, etre, taller, vouloir, and prendre are also covered in detail.
Part II focuses on past tenses, from the composition of the passe compose to its contrasting use with the imperfect tense. The formation and uses of the pluperfect and passe simple are also thoroughly.
Part III covers the future tenses (simple future, le future proche, and future perfect) and the conditional. The formation and uses of present and past subjunctive are explained, as well as the use of subjunctive in the main clause.
Part IV addresses the infinitive and negative infinitive, the imperative and negative imperative, the present participle and the gerund, and the formation and uses of the passive voice. " --Back cover
Includes index.
"Extensive audio recordings, vocabulary flash cards, review quizzes, and progress tests are available to support your study of this book. Go to the Apple app store or the Google Play store (for Android devices) to download the free Language Lab mobile app. A web version is also available online at: www.mhlanguagelab.com." --Verso t.p.
English and French.
Keywords: French language -- Verb -- Problems, exercises, etc..; French language -- Tense -- Problems, exercises, etc..; French language -- Textbooks for foreign speakers -- English